Economic impact of a vaccine preventable disease: a scoping review on tuberculosis - Mahmud, Aidalina; Aizuddin, Azimatun Noor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Using pulmonary tuberculosis (pTB) as an example of a vaccine-preventable disease (VPD), we aimed to gather evidence on the economic impact of treating a case or managing an outbreak of a VPD. A scoping review was con-ducted. Online databases (MEDLINE and Google Scholar) were used to collate published studies from the year 2015 to 2019 on the management cost of one case or an outbreak of pTB. Keywords used were cost, treatment, outbreak, pulmonary tuberculosis, tuberculosis, economic, economic evaluation. A total of 29 studies were analysed. The costs of pTB treatment for individual patient were higher in high-income countries compared to middle-income and low-income countries. A case of pTB can result in household catastrophic health expenditure; while an outbreak can overwhelm the health system’s capacity, and disrupts the economy of a country. Therefore, accessibility of vaccines especially in low-income countries must be ensured. Also, vaccine-hesitant individuals must reconsider their stance on vaccination.